GESTÃO DO ATIVO INTANGÍVEL NO SETOR PÚBLICO - Felipetto, Marta Raquel Zuchelli (2022)
The aim of the study was to analyze the effect of intangible assets on social responsibility and the impact on the effectiveness of municipal management. A case study was elaborated with a quantitative approach, descriptive procedure, based on the model proposed by Queiroz (2003). Data were collected through the application of questionnaires to those responsible for expenses and planning. Multivariate confirmatory analysis was used, through factor analysis and modeling with structural equations. The survey results showed that the components of intangible assets: human capital, internal organization, external relations and transparency are statistically significant for municipal management. With regard to the ability of social responsibility to mediate the relationship between intangible assets and the effectiveness of municipal management. It was found that it partially influences the results of actions taken. Also it was concluded that the Municipal Management Effectiveness Indicators proved to be significant, in order to indicate the relevance of intangible asset management and how this can contribute to improving the quality of service provision, the effectiveness of the management that will reflect, consequently, in the improvement municipal administration image. Theoritical contribution of the study is the identification of the significant influence of social responsibility as a mediating variable in the relationship between intangible assets and the effectiveness of municipal management, as well as complementing the model proposed by Queiroz (2003) for municipal management.